2014
DOI: 10.1111/gfs.12121
|View full text |Cite
|
Sign up to set email alerts
|

Performance and blood parameters when lambs and meat‐goat kids were finished on pasture with and without whole cottonseed (Gossypium hirsutum) supplementation

Abstract: We evaluated forage production patterns, weight gains and blood parameters when lambs (Ovis aries) and meat-goat (Caprus hircus) kids were finished on a mixed sward of cocksfoot (Dactylis glomerata L.), red clover (Trifolium pratense L.) and white clover (Trifolium repens L.) with (SUP) and without (UNSUP) supplemental whole cottonseed (Gossypium hirsutum; WCS) in a replicated study. Botanical composition and energy/protein ratios of the sward varied with year and with time during the growing season. Swards ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…Nonetheless, the increase in average daily gain (ADG) resulting from concentrate intake was considerable especially in the last 34 (56-90) days of the trial where growth rate of the supplemented goats was more than double that of the control goats. Meanwhile, the overall increase in ADG of more than 57% observed in both genotypes was higher than the 18% increment reported by Turner et al (2014) in Boer-crossbreds but similar to observations made by Haddad (2005) on growing Baladi goats fed varying proportions of forage to concentrate. The higher growth rate of M Â B crossbreds showed the genetic superiority of the Boer goat over the pure Mubende goat and this was consistent with previously reported results by Ssewanyana et al (2004).…”
Section: Growth Characteristicssupporting
confidence: 82%
“…Nonetheless, the increase in average daily gain (ADG) resulting from concentrate intake was considerable especially in the last 34 (56-90) days of the trial where growth rate of the supplemented goats was more than double that of the control goats. Meanwhile, the overall increase in ADG of more than 57% observed in both genotypes was higher than the 18% increment reported by Turner et al (2014) in Boer-crossbreds but similar to observations made by Haddad (2005) on growing Baladi goats fed varying proportions of forage to concentrate. The higher growth rate of M Â B crossbreds showed the genetic superiority of the Boer goat over the pure Mubende goat and this was consistent with previously reported results by Ssewanyana et al (2004).…”
Section: Growth Characteristicssupporting
confidence: 82%
“…Turner and others () evaluated lambs and goats grazing on mixed pasture (orchardgrass, red clover, and white clover) unsupplemented or supplemented with whole cottonseed. They found that supplementation with whole cottonseed increased Suffolk lamb carcass weights and rib area compared to unsupplemented animals, but for lambs of the Katahdin breed and goats no differences were found between treatments and this might reflect the higher consumption of the supplement by the Suffolk lambs than Katahdin lambs and goat kids (Turner and others ). Whole cottonseed and by‐products can be an alternative feed source of low cost (Paim and others ).…”
Section: The Effect Of Forage Plus Supplementation On Lamb Productionmentioning
confidence: 99%